1998
DOI: 10.1037/0022-3514.75.4.938
|View full text |Cite
|
Sign up to set email alerts
|

The process of inductive inference in groups: The use of positive and negative hypothesis and target testing in sequential rule-discovery tasks.

Abstract: Two experiments on the process of rule discovery in groups were conducted using a card deck and Wason number triple tasks. The positive effects of incentives on the proportion of correct hypotheses could not be explained by differential testing. The variables "hypothesis vs. target testing" and "small vs. broad range of rule" did not affect this proportion. There was a preponderance of positive tests, declining during trials. Negative tests occurred more often under the target test and broad rule range conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…But they can draw conclusions from the feedback they get after positive or negative tests. Crott et al (1998), McDonald (1990), and Penner and Klahr (1996) found that participants were in fact able to react differentially and adequately to these two relations. We expect that this will also be the case in the present experiment:…”
Section: Hoffmann and Crottmentioning
confidence: 94%
See 4 more Smart Citations
“…But they can draw conclusions from the feedback they get after positive or negative tests. Crott et al (1998), McDonald (1990), and Penner and Klahr (1996) found that participants were in fact able to react differentially and adequately to these two relations. We expect that this will also be the case in the present experiment:…”
Section: Hoffmann and Crottmentioning
confidence: 94%
“…Crott, Giesel, and Hoffmann (1998), Klayman and Ha (1989), Laughlin, Magley, and Shupe (1997), McDonald (1990), Penner and Klahr (1996), and Slowiaczek, Klayman, Sherman, and Skov (1992) found that participants reacted to certain experimental variations in a manner corresponding to Klayman and Ha's conclusions. These findings will be referred to in the following sections.…”
Section: Introduction and Predictionsmentioning
confidence: 91%
See 3 more Smart Citations